One health approach to Rickettsia spp.: Brazilian indigenous individuals, their dogs and ticks, and healthcare professionals - Louise Bach Kmetiuk; Vamilton Alvares Santarém; Daniele Rodrigues; Suelen Teixeira de Faria Resende; Isabella Braghin Ferreira; Rogério Giuffrida; Bianca Bárbara Fonseca da Silva; Lucianne Cardoso Neves; Raphaela Bueno Mendes Bittencourt; Leandro Meneguelli Biondo; Fabiano Borges Figueiredo; Felipe da Silva Krawczak; et al. (One Health)
Although Indigenous populations have historically overlapped the occurrence of vector-borne pathogens, no One Health approach study has investigated Rickettsia spp. in indigenous communities worldwide. Accordingly, the aim of this study was to investigate anti-Rickettsia spp. antibodies in indigenous individuals, their dogs and healthcare professionals, and Rickettsia spp. infection in ticks from ten indigenous communities of southern and southeastern Brazil. In overall, 66/771 (8.6 %) indigenous individuals, 9/99 (9.1 %) healthcare professionals and 116/386 (30.1 %) dogs were seropositive for at least one out four Rickettsia species tested by immunofluorescence assay (IFA). Out of 603 ticks collected from dogs in indigenous communities, 9/190 (4.7 %) tested positive to fragment of Rickettsia gltA gene by real-time PCR. The homologous antigenic reactions in dogs were significantly more frequent for R. bellii when compared to R. parkeri and R. amblyommatis and may be associated with the high diversity of hard and soft ticks in Americas, and R. bellii capacity of inhibiting another pathogenic rickettsia. Tick bite history increased the seropositivity (odds ratio = 9.29; p = 0.019) in healthcare professionals. This difference may be consequence of higher capacity to recognize tick bites by healthcare professionals, which highlighted the necessity of health care education for indigenous individuals for prevention and early recognition of tick-borne diseases in indigenous communities. In addition, the One Health approach herein has provided a holistic understanding of Rickettsia spp. infection in such communities and correspondent healthcare personal.